Greek and Latin Roots Part II - Greek - Smith, Peter; Open Textbook Library (Open Textbook Library, 2016)
Greek and Latin Roots: Part II - Greek is part two of a two part series. This series examines the systematic principles by which a large portion of English vocabulary has evolved from Latin and (to a lesser degree) from Greek. This book focuses on Greek roots. A link to the first part focusing on the Latin roots can be found below. Part II will try to impart some skill in the recognition and proper use of words derived from Greek. There is a stress on principles: although students will be continually looking at interesting individual words, their constant aim will be to discover predictable general patterns of historical development, so that they may be able to cope with new and unfamiliar words of any type that they have studied. They will be shown how to approach the problem by a procedure known as "word analysis," which is roughly comparable to the dissection of an interesting specimen in the biology laboratory. The text assumes no previous knowledge of Greek, and does not involve the grammatical study of this language-except for a few basic features of noun and verb formation that will help students to understand the Greek legacy in English. All students will be asked to learn the Greek alphabet. This skill is not absolutely essential for a general knowledge of Greek roots in English. However, it will help students understand a number of otherwise puzzling features of spelling and usage. Although there will be some attention paid to the historical interaction of Greek with English, this text is definitely not a systematic history of the English language. It focuses on only those elements within English that have been directly or indirectly affected by this classical language. In order to provide the broadest possible service to students, the text emphasizes standard English vocabulary in current use. The more exotic technical vocabulary of science and medicine can be extremely interesting, but is explored in only summary fashion. Nevertheless, this text should be of considerable value, say, to a would-be botanist or medical doctor, if only by providing the foundation for further specialized enquiry.
Preface to 5th Edition -- Foreword -- Chapter 15: The Greek Language -- Chapter 16: The Greek Noun (Declensions 1 and 2) -- Chapter 17: Compound Words in Greek -- Chapter 18: The Greek Noun (Declension 3) -- Chapter 19: Greek Adjectives and Adverbs -- Chapter 20: Numerals in Greek and Latin -- Chapter 21: Greek Prefixes -- Chapter 22: Greek Verbs and their Derivatives -- Chapter 23: Some Medical Terminology -- Appendix III - Key to Exercises (Greek) -- Appendix IV - Summary of Vocabulary Tables (Greek)
In English.
Description based on online resource
Keywords: Humanities -- Textbooks; Language and languages -- Textbooks